Inhibition of the CDK4/6-Cyclin D-Rb Pathway by Ribociclib Augments Chemotherapy and Immunotherapy in Renal Cell Carcinoma. (12th June 2020) - Chen, Dehong; Sun, Xiaosong; Zhang, Xuejun; Cao, Jun
Abstract : Renal cell carcinoma (RCC) is the most aggressive type of genitourinary cancer and is resistant to current therapies. Identifying drugs that enhance the efficacy of RCC standard-of-care drugs at sublethal concentrations is an alternative therapeutic strategy. Ribociclib is an orally available cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitor that is approved for the treatment of breast cancer. In this work, we demonstrate that ribociclib at clinically achievable concentrations inhibits proliferation of 7 out of 9 tested RCC cell lines, with IC50 range from 76 to 280 nM. In addition, ribociclib induces apoptosis of RCC cells, but with less potency compared to its antiproliferative activity. The combination of ribociclib with chemotherapeutic or immunotherapeutic agents is synergistic in RCC cell lines. Of note, ribociclib demonstrates selective anti-RCC activity by sparing normal kidney cells and fibroblast cells. Consistent with the in vitro findings, ribociclib inhibits RCC growth at the dosage that does not lead to toxicity in mice and enhances the in vivo efficacy of RCC standard-of-care drugs. Mechanistically, we show that ribociclib remarkably inhibits phosphorylation of retinoblastoma protein (Rb) at various sites, leading to the suppression of transcription of E2F target genes in RCC cells. Our findings clearly demonstrate the potency and selectivity of ribociclib in RCC preclinical models, via inhibition of the CDK4/6-cyclin D/Rb pathway. Our findings support a clinical trial for the combination of ribociclib with chemo/immunotherapy in RCC.